Climate change and social responsibility - Crowther, David; Singh, Rubee; Joshi, Amit; Kumar, Vikas (Emerald Publishing Limited, 2025)
Climate Change and Social Responsibility explores the complex relationships between climate change and social responsibility, offering a unique blend of historical context, future perspectives, and innovative solutions. This book examines the political, economic, and social dimensions of climate change, from the role of governments and international institutions to the impact on human migration and sustainable business models. This is a must-read for scholars, policymakers, business leaders, and practitioners seeking to understand the complexities of climate change and social responsibility. Its interdisciplinary approach and global perspective make it an invaluable resource for anyone working towards a more sustainable and equitable future. With its rich insights and expert analysis, Climate Change and Social Responsibility is a call to action for individuals, organizations, and governments to embrace their social responsibility and join the quest for a climate-resilient world. The Developments in Corporate Governance and Responsibility series offers the latest research on topical issues by international experts and has practical relevance to business managers.
Includes index.
Keywords: Social responsibility of business.; Business & Economics -- Leadership.; Business ethics and social responsibility.; Management: leadership and motivation.; elektronické knihy; electronic books